ECONOMIC ANALYSIS OF MARKETING WHITE SKINNED SWEET POTATO (Ipomoea batatas) IN SELECTED MARKETS OF KANO STATE, NIGERIA. (FUDMA JOURNAL OF SCIENCES, 2020)
The study focused on the analysis of marketing White skinned Sweet Potato in selected markets of Kano State. Multistage sampling techniques was used for the study and data was collected using a structured questionnaire supplemented with key informant interview. A total of one hundred and seventeen 117 white sweet potato marketers were sampled. The analytical tool employed included simple descriptive statistics, net marketing margin, Gini Coefficient, marketing efficiency and multiple regression of the respondents in the study area. The result of the socio economic characteristics showed that 33% of the white sweet potato marketers were adult belonging to the age group of 30-39 years, 60% of marketers had household size of 1-10 members, 41% had 1-10 years of marketing experience, 91% were married with 91% males, the result of educational background study area shows that 46.8% had informal education. The result of the profitability analysis revealed that white sweet potato marketing was profitable with â‚¦574.52 and the total revenue realized for the marketing were â‚¦3,829.06. The result further revealed Gross Margin (GR) of 0.85 traded in the study area while return per naira invested was found to be 1.18 accrued from every 1.00 invested. The result also revealed that marketing of white sweet potato was efficient with 225.27%. The study further revealed variables such as: marketing experience, labour costs, transportation costs, loading and off-loading were found to be statistically significant. Results also indicate that the major determinant of net marketing income in the study area included labour
Keywords: Multistage sampling; potato; descriptive statistics; profitable analysis; marketing